PENGELOLAAN KAWASAN KARST DI KALIMANTAN SELATAN - Sugiyanto, Bambang (Naditira Widya, 2008)
The karst environment is a unique natural phenomenon, which provides abundant resources for human survival, such as minerals, birds nest, guano, and forest products. Beside natural resources, the karst environment also store cultural resources essensial to archaeological i.e. caves or rock shelters, which once occupied by prehistoric human. Therefore, it is important to be able to preserve the karst environment, either natural or cultural, for the benefit to the next generation. In order to carry out an appropriate karst environment management, especially in South Kalimantan, coordination and collaboration should be established between the Centre for Archaeology, Banjarmasin, the Local office for Culture and Tourism, the Conservation Centre for Natural Resources, the Lambung Mangkurat University, the non government organization on culture and the South Kalimantan community and produce a policy as a legal instruction to protect and preserve the South Kalimantan natural resources. This article discusses the strategy pf preservation-based karst environment management in South Kalimantan.